2017
DOI: 10.1371/journal.pone.0177371
|View full text |Cite
|
Sign up to set email alerts
|

Timelines of translational science: From technology initiation to FDA approval

Abstract: While timelines for clinical development have been extensively studied, there is little data on the broader path from initiation of research on novel drug targets, to approval of drugs based on this research. We examined timelines of translational science for 138 drugs and biologicals approved by the FDA from 2010–2014 using an analytical model of technology maturation. Research on targets for 102 products exhibited a characteristic (S-curve) maturation pattern with exponential growth between statistically def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 34 publications
2
61
1
1
Order By: Relevance
“…Thus, drug development becomes significantly more efficient once the associated technology passes the established point. Finally, our data suggest that the time between a scientific insight, or invention that gives rise to a new area of research, to approval of products based on this technology is 36 years, 29 an interval similar to that described by others looking at the elapsed time between seminal publications and drug approvals. 30 …”
Section: Patterns Of Innovation In Biopharmaceutical Developmentsupporting
confidence: 75%
See 3 more Smart Citations
“…Thus, drug development becomes significantly more efficient once the associated technology passes the established point. Finally, our data suggest that the time between a scientific insight, or invention that gives rise to a new area of research, to approval of products based on this technology is 36 years, 29 an interval similar to that described by others looking at the elapsed time between seminal publications and drug approvals. 30 …”
Section: Patterns Of Innovation In Biopharmaceutical Developmentsupporting
confidence: 75%
“…25,[27][28][29] From these studies, we have shown that the accumulation of knowledge regarding specific biotechnologies, drug classes, or drug targets, as measured by the cumulative number of publications in PubMed, follows a S-curve growth pattern that can be modeled with an exponentiated logistic function (Figure 1). Using a nonlinear least squares fit of this function to the cumulative publication counts, we identify an initiation point (Ti) corresponding to the point of maximum acceleration of publication activity (max d 2 N/dt 2 ), and an established point (Te) corresponding to the point of maximum slowing of publication activity (min d 2 N/dt 2 ).…”
Section: Patterns Of Innovation In Biopharmaceutical Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Man muss jedoch bedenken, dass neue Erkenntnisse aus genetischen Studien für komplexe Netzhautdegenerationen zum Teil erst seit Kurzem bekannt sind, was deren therapeutische Umsetzung erst in der nähe-ren Zukunft erwarten lässt. So braucht es durchschnittlich mehr als 40 Jahre von der ersten Beschreibung eines Prozesses bis zur Markteinführung eines darauf aufbauenden Medikaments [36]. Auch könnte das Wissen um genetische Risikovarianten nur einen begrenzten Einfluss auf einen Therapieerfolg haben [37], zumal eine Risikovorhersage von komplexen Erkrankungen naturgemäß fehlerbehaftet ist [29,38].…”
Section: Die Rolle Der Genetik Von Netzhautdegenerationen Bei Der Theunclassified